2011
DOI: 10.31018/jans.v3i1.169
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of Lagenaria siceraria (Mol.) Standley, against certain bacteria and fungal strains

Abstract: Abstract:This study was performed to evaluate the antibacterial and antifungal potency of Lagenaria siceraria (Mol.) Standley, commonly known as bottle gourd belonging to the family Cucurbitaceae. Petroleum Ether, Chloroform, Methanol, Absolute alcohol and Water showed a majority of the compound including Steroids, Alkaloids, Tannins, Flavonoids, Lactones and Carbohydrates. All the five extracts were prepared by using soxhlet apparatus and the extracts showed moderate to potent antimicrobial activity against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Moreover, the broth microdilution assay demonstrated general agreement with the disc diffusion results, which proved that chitosan nanoparticles loaded with Lagenaria siceraria or Thymus vulgaris are potent antibacterial agents against P. aeruginosa and VRSA strains with MIC values of 0.125-2 µg/mL and 1-8 µg/mL, respectively. Regarding the results obtained by Nagaraja and coauthors [55], L. siceraria had an antimicrobial activity against S. aureus with an MIC value of 0.25 × 10 3 mg/mL, which differs from Diniz et al [56], who found that thyme oil showed lower inhibitory activities against P. aeruginosa with MIC values ranging from 64 to 512 µg/mL. However, Keawchaoon and Yoksan [28] confirmed that chitosan nanoparticles with carvacrol exhibited antimicrobial activities against S. aureus compared to chitosan nanoparticles alone.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the broth microdilution assay demonstrated general agreement with the disc diffusion results, which proved that chitosan nanoparticles loaded with Lagenaria siceraria or Thymus vulgaris are potent antibacterial agents against P. aeruginosa and VRSA strains with MIC values of 0.125-2 µg/mL and 1-8 µg/mL, respectively. Regarding the results obtained by Nagaraja and coauthors [55], L. siceraria had an antimicrobial activity against S. aureus with an MIC value of 0.25 × 10 3 mg/mL, which differs from Diniz et al [56], who found that thyme oil showed lower inhibitory activities against P. aeruginosa with MIC values ranging from 64 to 512 µg/mL. However, Keawchaoon and Yoksan [28] confirmed that chitosan nanoparticles with carvacrol exhibited antimicrobial activities against S. aureus compared to chitosan nanoparticles alone.…”
Section: Discussionmentioning
confidence: 88%
“…Concerning antifungal activity, the degree of growth inhibition was notably higher for Aspergillus flavus and Aspergillus oryzae, while the inhibition of growth was comparatively lower in the case of Trichoderma harzianum. (Ameen et al, 2022;Nagaraja et al, 2011) showcasing their potential as innovative and effective agents in combating microbial infections.…”
Section: Antimicrobial Properties Of Cucurbitaceae Speciesmentioning
confidence: 99%
“…The fruit of L. siceraria is used, in traditional medicine, as remedy for different diseases, which include fever, jaundice, cough, pectoral, asthma and other bronchial disorders (Shah et al, 2010;Aslam and Najam, 2013;Prajapati et al, 2010). The leaf, fruit peel and seed extracts of the plant have been shown to possess antimicrobial activities against a number of microorganisms (Goji et al, 2006;Badmanaban and Patel, 2010;Rodge and Biradar, 2012;Nagaraja et al, 2011). In phytochemical studies, a variety of chemical constituents have been isolated, which include flavonoids, triterpenoids and glycosides (Kumar et al, 2012;Gangwal et al, 2010).…”
Section: Introductionmentioning
confidence: 99%